MANAJEMEN STRATEGIK DALAM MENINGKATKAN KINERJA PEGAWAI PADA KANTOR INSPEKTORAT KABUPATEN SUMBAWA - Darma, D; Purwadinata, Subhan (Fakultas Ekonomi dan Manajemen, 2023)
This study aims to examine the application of strategic management in improving employee performance at Inspectorate Office of Sumbawa District. This study used a qualitative descriptive research approach. The data used in this study is qualitative in the form of information regarding the implementation of strategic management in improving employee performance at Inspectorate Office of Sumbawa District. The researchers obtained qualitative data directly from several informants who served as sources. The numbers of informants in this study were four informants, consisting the Inspector Inspectorate Office of Sumbawa District and the Head of Subdivision at Inspectorate Office of Sumbawa District totaling three people. The data analysis in this study uses the Miles and Huberman qualitative data analysis technique which consists of three activity streams that occur simultaneously, namely: data reduction, data presentation, and verification/ conclusions. The results of study showed that the implementation of strategic management at Inspectorate Office of Sumbawa District had been done well so that employee performance can be improved. Strategy planning was the initial stage before carrying out activities which aims to design the work program that will be implemented so that it can run optimally, strategy implementation had been done well in accordance with the Annual Supervision Work Program (ASWP) and strategy evaluation had been done once in one year in order to measure the improving of employees performance.